Contesting the boundaries of religion in social mobilization - Graham K. Brown; Séverine Deneulin; Joseph Devine (University of Bath, Centre for Development Studies (CDS), 2009)
This paper seeks to contribute to an understanding of the dynamics of religion in social mobilization. It argues that existing approaches to the study of the role of religion in social mobilization have been insufficiently nuanced and have failed to probe the multiple and often contradictory influences that religion can have on mobilization channels. On the basis of three qualitative case studies, from Malaysia, Bangladesh and the United Kingdom, we identify three key ingredients for religion to act as a catalyst for social mobilization: theological resources, sacred spaces, and their interaction with the wider context. This leads us to conclude that the boundaries of the 'religious' dimension of social mobilization are fluid, and that the religious element of social mobilization can never be disentangled from its social and political context.
Keywords: 330; Religion; social mobilization; theology; politics